2007
DOI: 10.2475/03.2007.03
|View full text |Cite
|
Sign up to set email alerts
|

Tracking crystallinity in siliceous hot-spring deposits

Abstract: Siliceous hot spring deposits (sinters) entrap paleoenvironmentally significant components and are used as extreme-environment analogs in the search for early Earth and extraterrestrial life. However, sinters undergo a series of textural and mineralogical changes during diagenesis that can modify and overprint original environmental signals. For ancient hydrothermal settings including those close to the dawn of life, these transformations have long since occurred, so that study of diagenetic processes and effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 67 publications
6
54
0
Order By: Relevance
“…10). This process has been well documented in low-temperature siliceous sinters (Lynne et al, 2007;Day and Jones, 2008). We interpret the presence of residual silica hydrates (opal and moganite) as evidence that the euhedral quartz microcrystals at El Indio evolved from a hydrous, metastable precursor.…”
Section: Evolution Of Quartz Microcrystals From Silica Hydratementioning
confidence: 86%
See 1 more Smart Citation
“…10). This process has been well documented in low-temperature siliceous sinters (Lynne et al, 2007;Day and Jones, 2008). We interpret the presence of residual silica hydrates (opal and moganite) as evidence that the euhedral quartz microcrystals at El Indio evolved from a hydrous, metastable precursor.…”
Section: Evolution Of Quartz Microcrystals From Silica Hydratementioning
confidence: 86%
“…1F-H; doubly terminated crystals and clusters of euhedral quartz microcrystals) are similar to those of quartz evolved from metastable silica hydrate in silica sinters from hot spring environments at ~ 100 °C (e.g. Lynne et al, 2007). The euhedral El Indio quartz microcrystals exhibit distinct α-quartz morphology, indicating that the final stage of crystallization of euhedral quartz from precursor material occurred at <573°C.…”
Section: Morphologymentioning
confidence: 90%
“…Previous studies on silica sinters have shown that the thermodynamically unstable opal-A matures and transforms over time, forming thermodynamically more stable paracrystalline [47] opal-CT, then opal-C, and ultimately blocky, microcrystalline quartz [51,54,55,[59][60][61][62][63]. In the case of the Taupo Volcanic Zone in New Zealand, microcrystalline quartz becomes a common phase in silica sinters older than~20,000 years [51].…”
Section: Formation and Recrystallization Of Noncrystalline Silica In mentioning
confidence: 98%
“…The transformation from opal-A to opal-CT is typically accompanied by textural changes [51,54,55,58,59], although the mineralogical changes may outpace textural maturation [63,65]. Opal-CT commonly forms lepispheres that are similar in size to the opal-A microspheres [51,[54][55][56]58,59].…”
Section: Formation and Recrystallization Of Noncrystalline Silica In mentioning
confidence: 99%
See 1 more Smart Citation